Dinâmicas da circulação intermidiática: análise de fluxos imagéticos e perlaboração de imaginários - Ferreira, Mylene (Universidade do Vale do Rio dos Sinos, 2019)
This study deals with the dynamics of the intermediary circulation (FERREIRA; ROSA, 2011), having the communication process by imagetic flows involving Petrobras as a privileged phenomenon for the observation of marks of the environment in which we live, a society in the process of mediatization (GOMES, 2017). We take as research case the articulations between the (co) advertising, journalistic productions and the manifestations of social actors interacting in media devices (FERREIRA, 2006). We observe how the associations of meaning, especially the imagery metaphors, are operationalized until the construction of what we consider as image-synthesis (ROSA 2012). A qualitative and semiological project (VERÓN, 1997; 2014; FERREIRA, 2013; 2016), presented through an imagetic and analytical mapping of one of the possible approaches involving Petrobras from 2014 to 2018. As a research problem the search to understand how the communicative process in focus was presented and constituted, and for that they are established as key questions: How do the meaning associations about Petrobras operate in the intermediary circulation to mean the company? And, how do these associations relate to attempts to update the social and symbolic imaginary linked to the company, given the impact of the mediatization process? Using the indicative (BRAGA, 2008) and abductive (SEBEOK; UMIKER-SEBEOK, 2014) method, two communication circuits (BRAGA, 2012) are constituted: “Storm” and “Reinvention”. These are circuits analyzed by both textual and figurative image flows (VERÓN, 2004). With the images considered in “flow ahead” (BRAGA, 2012), with intelligibility conferred by operations performed in the circulation process (ROSA, 2012), we pursue the following specific objectives: a) to seek articulations of meanings and imagery references about Petrobras , with historical symbolics and fragments of the organizational imagination being debated and updated between 2014 and 2018; b) identify, in the dynamics of the intermediary circulation, the Tempest and Reinvention communication circuits, being formed by materialities - from heterogeneous sources and formats, operationalized in imagetic flows; c) to perceive mediatization marks in the discursive processualism observed, involving production and recognition of meanings about Petrobras, coming from both the organization itself, as productions of journalistic institutions and manifestations of social actors interacting in media devices. Observing the profusion of meanings, media operations are outlined both to propose, question and / or (re) build Petrobras's foundational symbolic (CASSIRER, 1994), as well as traces of an imaginary / symbolic perlaboration that - inspired by the triad “remember, forget, working through” of Freud (1914), lead us to proposals of updates of the social imagination (CHARAUDEAU, 2006; 2017) for a widely communicated, spoken and “communicating” organization (BALDISSERA, 2009). We seek here to portray a complex social process, with imaginary circularities (ROSA, 2012) that appear and disappear continuing the case, which ends up being exasperated (FORD, 1999; 2002), that is, a case alive in the unpredictable sea. of mediatization.
Keywords: Midiatização; Imagem; Circulação midiática; Petrobras; Organização; Mediatization; Image; Media circulation; Organization; ACCNPQ::Ciências Sociais Aplicadas::Comunicação